2023
DOI: 10.3390/vaccines11010194
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Is Not Associated with Psychiatric Adverse Events: A Meta-Analysis

Abstract: Coronavirus disease 2019 (COVID-19) has been a global health problem since December 2019. Vaccination has been widely considered the best way to prevent COVID-19 pandemic, but public concerns about the safety of vaccines remain. There have been many studies reporting adverse events in the vaccinated. However, to date, no meta-analysis of the association of COVID-19 vaccination with psychiatric adverse events has been conducted yet. In this meta-analysis, studies on depression, anxiety and distress after COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(108 reference statements)
0
0
0
Order By: Relevance
“…A recent meta-analysis conducted by Lee et. al concludes a similar finding indicating that there is no significant association between COVID-19 vaccination and depression as well as anxiety [11] . The meta-analysis included 6 studies and concluded only a 4% reduction in distress after receiving the vaccine shown in overall studies.…”
Section: Discussionmentioning
confidence: 80%
“…A recent meta-analysis conducted by Lee et. al concludes a similar finding indicating that there is no significant association between COVID-19 vaccination and depression as well as anxiety [11] . The meta-analysis included 6 studies and concluded only a 4% reduction in distress after receiving the vaccine shown in overall studies.…”
Section: Discussionmentioning
confidence: 80%
“…Existing related studies did not scrutinize the gender difference in the vaccination effects on mental health [26][27][28]30]. Any gender difference in the vaccination effect was not found [25,29], while vaccinated females showed lower anxiety symptoms than those not vaccinated [30]. Different from these studies, we put focus on gender differences to explore the comprehensively subjective probability of getting COVID-19 and mental health conditions.…”
Section: Discussionmentioning
confidence: 91%
“…We created the dummy variables, VACCINE SECOND_1 to VACCINE SECOND_4, to capture the timing of the second shot. Although their mean values may seem quite low, this is because we set the value of these variables before the 12th survey (28)(29)(30)(31) May 2021) at zero, reflecting the reality in Japan. On 23 April 2021, as of the 11th survey (23-26 April 2021), the percentage of vaccinated individuals was 0.23% and 0.00% for the first and second shots, respectively.…”
Section: Concerning Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation